TUNTUTAN PEKERJAAN DAN STRES KERJA SEBAGAI VARIABEL PENENTU TURNOVER INTENTION - Andriani Nugraha; Sylvia Diana Purba (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2017)
This study aims to explore the effect of job demands on turnover intention with job stress as mediating variable on employees that have been working less than sixth years. Sampling method used is the purposive-non probability sampling, where 100 employees of head office PT. Adhi Karya (Persero) Tbk were taken as respondents. Method of data analysis used is path analysis, the simple mediation model. Data were processed with macro and syntax from Preacher-Hayes 2013. The results of this study indicates that the effect of job demands on turnover intention was not mediated by job stress. Job demands and job stress influence significantly toward turnover intention, but job demands have no significant impact on job stress.